Perbandingan Teknik Isolasi DNA pada Daun dan Kayu Sonokeling (Dalbergia latifolia) - Susila, Susila; I Putu Gede P. Damayanto; Kusumadewi Sri Yulita; Nawwall Arrofaha (MANILKARA: Journal of Bioscience, 2024)
Rosewood (Dalbergia latifolia) is a hardwood plant, resistant to termite attack, its wood has beautiful patterned fibers and textures, so it is widely used for furniture in luxury categories with high economic value. According to CITES (Convention on International Trade in Endangered Species of Wild Fauna and Flora), rosewood trade status is included in appendix II. In the trade of rosewood in both domestic and international markets, there are relatively many obstacles and difficulties in identifying the origin of rosewood. It is very important to establish a reference on the identity of wood based on the location of origin as an effort to prevent illegal trade, namely by using a molecular-based identification approach (DNA fingerprinting). In the isolation of rosewood DNA, special techniques are required due to its hard wood characteristics. This study aims to compare DNA isolation techniques from wood and leaves of rosewood using the CTAB (Cetyl Trimethyl Ammonium Bromide) protocol and the commercial kit protocol. The research used molecular biology-based identification methods. PCR results showed that the DNA isolation protocol using the commercial kit outperformed the CTAB protocol for both leaf and wood samples. DNA isolation from wood samples was more difficult than leaf samples. Overall, the best protocol for DNA isolation from rosewood leaves and wood was to use a commercial kit.